A money-based indicator for deflation risk - Roberta Colavecchio; Gianni Amisano; Gabriel Fagan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We employ a money-based early warning model in order to analyse the risk of a low inflation regime in the Euro Area, Japan and the US. The model specification allows for three different inflation regimes: "Low", "Medium" and "High" inflation, while state transition probabilities vary over time as a function of monetary variables. Using Bayesian techniques, we estimate the model with data from the mid 1970s up to the present. Our analysis suggests that the risks of a "Low" inflation regime in the Euro Area have been increasing in the course of the last six quarters of the estimation sample; moreover, money growth plays a significant role in the assessment of such risks. Evidence for Japan and the US shows that for both countries the inclusion of an indicator variable does not substantially change the assessment of the risk of a "Low" inflation regime.
Keywords: C11; C53; E31; 330